The curious case of T-cell mediated renal allograft rejection after Covid-19 infection - Keya Basu; Subhrajyoti Karmakar; Sougata Dasgupta; Moumita Sengupta (Wolters Kluwer Medknow Publications, 2024)
Our case illustrates the possible explanation of renal allograft rejection in a patient who had recovered from Covid-19 infection in the post-transplant period, which ultimately led to the death of the patient. A 27-year-old male patient received renal allograft from his mother, with an uneventful post-transplant period. Three years after the transplantation he contracted Covid-19 infection. The patient recovered from Covid-19 infection after being treated according to the treatment protocol. Subsequently, in the next 2 weeks, he presented with heavy proteinuria and a rise in serum creatinine level. Renal biopsy examination showed features of acute T-cell mediated rejection (TCMR) without any evidence of antibody-mediated rejection. He was given all due care but he deteriorated quickly leading to his death. This case highlights the inter-relation between Covid-19 infection and acute TCMR of the renal allograft, where renal biopsy serves as an indispensable tool in understanding its pathophysiology.